Peningkatan Kinerja Keputusan Pembelian melalui Penilaian Kesadaran Merek, Asosiasi Merek, Loyalitas Merek dan Persepsi Kualitas menggunakan Metode Regresi Ganda: Studi Kasus Pembelian Truk di PT AIIS - Susanto, Novie; Rinawati, Dyah Ika; Ramadhani, Fery (TEKNIK, 2019)
Sales data and market share of a truck product called ILT in PT AIIS continues to decline during period 2014-2016. Based on these findings, this research examines how sales and market share of the truck could be improved. This research aims to examine the influence of brand awareness, brand association, perceived quality, and brand loyalty to the purchasing decision of ILT in PT. AIIS. The analysis technique uses multiple regression analysis. From the research result, it is found that only the brand awareness and perceived quality variables that positively and significantly influence the purchasing decision of ILT where brand awareness is the dominant factor that influences purchasing decisions. Adjusted R Square value of 0,521 indicates that 52.1% of variation of purchasing decision can be explained by four independent variables in regression equation while the rest equal to 47,9% explained by other variables which were not examined in this research.